Webquest : The Transformation and Innovation in ELT - Langgeng Budianto (JETLe (Journal of English Language Teaching and Learning), 2020)
This paper aims at describing the use of modern technology for language teaching.The idea of webquest in language teaching has had colossal changes in recent decades. Advancements in technology, the prominence of the internet and its simple accessibility in numerous parts of the world has made a suitable device for teacher improvement. Web based media place new requests with respect to language which can advance varieties in language utilized (Halliday, 1990). The core issue of this paper will surely encourage the language teachers to find out the interesting and beneficial method of teaching and learning in the academic English classroom. Thus, the use of webquest in language teaching is one effective tool to promote variations in language teaching. The five main components of Webquest, namelythe introduction, task, process, resources, evaluation, and conclusion are significatlyinnovative teaching and learning strategies in EFL context.